AGRICULTURE: A PANACEA TO ECONOMIC GROWTH AND DEVELOPMENT IN NIGERIA - Oluwole, Israel Oluwasani; Attama, Paulinus Ikechukwu; Onuigbo, Fidelia Nebechi; Atabo, Ichaba (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
Economic growth and development is critical to every economy, therefore making it imperative to understand why government policies fail or succeed, in other to learn on best ways to spur economic growth and development. According to Maslow’s hierarchy of need, food is one of the basic needs of man, thereby making food security first a priority for every economy, while export of excess provides a source of foreign earning for a country like Nigeria which export primary products. With double digit food inflation, balance of payment necessitated from sub-optimal export from the non-oil sector. This study examined agriculture: a panacea to economic growth and development in Nigeria in relation with GDP growth, towards understanding causal relationship, if any, between agricultural sector GDP growth and development. Scholars have diverse views on how to rehabilitate the Nigerian economy. The paper utilized documentary methods to source for materials and analyzed using content analysis technique. In doing this, Basic Resource Theory was used as a framework of analysis to address the issue. The paper also examined the various challenges facing Nigerian state in achieving this economic growth and the core is the oil. The findings among others found out that agriculture is a solution to economic growth and that the discovery of crude oil served as the major contributor in neglecting Agriculture as a means of economy in Nigeria. Thus, based on the findings of this paper it recommended among that there is need for effective monitoring of allocated funds, to ensure that there is no shortfall in remittance and to equally conduct an audit overtime to ensure judicious management of allocated funds until the project is completed. This will see to the lasting solutions to sustainable economic growth and development in Nigeria.